Mengembangkan Pemasaran Digital dalam Meningkatkan Efisiensi dan Produktivitas Penjualan pada UMKM “Kakanan Dhisa” di Desa Trebungan, Situbondo - Tarisa Amalia; Agus Supriono; Yuli Hariyati; Cindera Rosa Damascena (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
Advances in information technology have significantly transformed the business landscape, including for Micro, Small, and Medium Enterprises (MSMEs). Digital transformation has become a necessity for MSMEs to expand their markets, build their brands, and enhance customer engagement. While the benefits of digital transformation have been widely felt by MSMEs in urban areas, rural MSMEs face challenges due to limited knowledge of digital technology. As a result, their ability to compete in modern markets is hindered, and they remain reliant on local consumers. As a solution, empowerment efforts are needed through SME mentoring activities aimed at developing digital marketing capabilities. The empowerment program was implemented for the “Kakanan Dhisa” SMEs in Trebungan Village, Situbondo. The program consisted of three phases: planning and preparation, implementation, and evaluation, spanning six weeks from July to August 2023. The results show that MSME operators gained a better understanding of digital marketing tools and were able to independently enhance their online promotional capabilities. This empowerment program not only supports the capacity building of MSME operators but also contributes to the achievement of the Sustainable Development Goals (SDGs), particularly goal 1 & 4.